2019
DOI: 10.15395/mkb.v51n2.1456
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Mid-Regional Pro-Adrenomedullin and Sequential Organ Failure Assessment (SOFA) Score in Patient with Sepsis

Abstract: AbstrakMost sepsis will develop into multi organ failure (MOF). To assess manifestation of MOF, SOFA score that includes several laboratory parameters for each organ is used. However, this requires time and is also costly. Recently, Mid-Regional Pro-Adrenomedullin (MR proADM) biomarkers are stated to be an alternative marker of MOF in sepsis because MR proADM is secreted by endothelials that may increase in sepsis or bacterial infection. The aim of this study was to analyze the correlation between serum MR pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous research showed this molecule had several roles in sepsis pathophysiology. As a prognostic biomarker, it has shown high concordance with SOFA, pediatric SOFA and PELOD score 9,10 . Unfortunately, this peptide has short half-life, which only 22 minutes in circulation 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed this molecule had several roles in sepsis pathophysiology. As a prognostic biomarker, it has shown high concordance with SOFA, pediatric SOFA and PELOD score 9,10 . Unfortunately, this peptide has short half-life, which only 22 minutes in circulation 8 .…”
Section: Introductionmentioning
confidence: 99%